Numerical Simulation of Backfilling Construction for Underground Reinforced Concrete Grain Silos - Longfei Yue; Guixiang Chen; Chenxing Cui; Chaosai Liu; Boyi Zhao (Buildings)
Food security is an important guarantee for national security and public health. Underground reinforced concrete (RC) grain silos can provide a quasi-low temperature environment for grain storage, effectively ensuring the quality of the stored grain. The stress status of the underground silo during soil backfilling construction is complex, which puts the structure at risk of failure. The present study developed a numerical simulation method to investigate the mechanical properties of underground silos during backfilling construction processes. A finite element (FE) analysis of the backfilling construction process of an underground RC grain silo was conducted, and the nonlinear contact between the underground silo and the surrounding soil, as well as the material nonlinear behavior of the soil, was considered. The deformation characteristics and stress distribution of the underground silo during the backfilling construction process were revealed. The results indicate that the underground RC grain silo exhibits good mechanical performance. The underground silo underwent overall settlement during the backfilling construction process, with a total settlement of 21 mm. The maximum radial displacement of the silo wall and the maximum deflection of the radial primary beam were 0.84 mm and 5.67 mm, respectively, both of which were smaller than the limit values. After the completion of backfilling construction, there was a high risk of concrete cracking of the silo wall. The maximum radial and circumferential tensile stresses of the concrete at the silo top were both high, which led to cracking in the top of the silo. Our research results provide important support for the design and evaluation of underground RC grain silos.